2020
DOI: 10.1016/j.jebo.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Models of intragroup conflict in management: A literature review

Abstract: The study of intragroup dynamics in management studies views conflict as a contingency process that can benefit or harm a group based of characteristics of the group and context. We review five models of intragroup conflict in management studies. These models include diversity-conflict and behavioral negotiation models that focus primarily on conflict within a group of people; social exchange and transaction cost economics models that focus primarily on conflict within a group of firms; and social dilemma mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 226 publications
(221 reference statements)
0
7
0
Order By: Relevance
“…Pfeffer and Salancik (1978) pointed that conflict resolutions among interest groups constrain inter-organizational actions. Firms can establish more independence by using suitable conflict management style to reduce their dependence on resources from other partners (Mccarter et al, 2018). That is to say, conflict management styles may change the power that yields control of other factors or resources, reducing constraints in the external environment (Grandori, 1991;Scott and Davis, 2013) and thereby influencing the level of firm's achieved earnings from OI.…”
Section: Different Conflict Management Stylesmentioning
confidence: 99%
“…Pfeffer and Salancik (1978) pointed that conflict resolutions among interest groups constrain inter-organizational actions. Firms can establish more independence by using suitable conflict management style to reduce their dependence on resources from other partners (Mccarter et al, 2018). That is to say, conflict management styles may change the power that yields control of other factors or resources, reducing constraints in the external environment (Grandori, 1991;Scott and Davis, 2013) and thereby influencing the level of firm's achieved earnings from OI.…”
Section: Different Conflict Management Stylesmentioning
confidence: 99%
“…These strategies would help minimize the destructive effects of the conflicts and improve their constructive effects on the project deliverables. McCarter et al (2020) discussed the management of intragroup conflicts by adopting three conflict management models: diversityconflict, behavioral Managing intragroup conflicts negotiation and social dilemma models. Heenkenda and Chandanie (2012) revealed that in Sri Lanka, conflicts that occur in building construction using traditional separated procurement and design and build procurement systems can be minimized by having a separate party for project management and coordination.…”
Section: 3mentioning
confidence: 99%
“…Van Lange et al ([ 25 ], p. 126) define the resulting social dilemma as: “a situation in which a non-cooperative action is (at times) tempting for each individual in that it yields superior (often short-term) outcomes for self, and if all pursue this non-cooperative course of action, all are (often in the long-term) worse off than if all had cooperated”. Highest collective and individual outcomes often occur when all partners choose to cooperate, the dilemma is that for cooperative behavior to make sense individuals must believe that the partner will cooperate as well [ 1 , 24 , 26 30 ]. Social dilemmas have frequently been used to model situations within society at large that involve interdependent actions [ 22 ] (for reviews see [ 25 , 31 ]), but they can also model behavior in business contexts, both within firms and between firms.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Concerns about future consequences (e.g. the shadow of the future) can affect whether individuals choose to maximize the long-term or short-term consequences of their actions [ 16 , 26 , 30 , 44 , 48 51 ] and whether they trust the cooperative intentions of others [ 21 ]. Hence, single interactions or repeated interactions can impact the willingness to cooperate and the ability to familiarize and learn from others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%